Bref aperçu des Actes de Bartalomēwos moine stéphanite du XVe siècle - Beylot, Robert (Aethiopica, 2000)
Bartalomēwos, an Agame monk and Emperor Zarʾa Yāʿqob’s teacher before his accession to the throne, was a disciple of the monk Esṭifānos (1397/98–1444) who was a famous leader of a religious and political dissident group. He suffered pains and was eventually tortured to death after 1444 for refusing to prostrate himself before the sovereign, as Esṭifānos had taught him.